Probe geometry and surface roughness effects in microscale impact testing of WC-Co. Issue 7 (18th May 2020) - Beake, B.D.; Isern, L.; Harris, A.J.; Endrino, J.L.
ABSTRACT: Depth-sensing repetitive microimpact tests have been performed on cemented carbide cutting tool inserts with spheroconical diamond probes with end radii of 8, 20 and 100 µm. Results were strongly dependent on the probe radius and applied load. At higher load, there was a transition to a faster damage rate marking the onset of more variability in rate and in the residual depth of the impact crater when using 8 and 20 µm probes. SEM images show the breakup of the WC skeleton at the periphery of the contact zone. Lower surface roughness slowed the initial damage rate at a higher load but did not significantly influence the final crater depth. The load-dependent fatigue mechanism displayed by the cemented carbide also has implications for the study and optimization of coatings when these are deposited.